(untitled) - Booysen, Vernon

Investigating prolificacy as a trait to sustainability in smallholder sheep farming systems in South Africa (Stellenbosch : Stellenbosch University, 2023)
Thesis (MScAgric)--Stellenbosch University, 2023.